Role of AMPK in autophagy - Wang, Shengyuan; Li, Hongyan; Yuan, Minghao; Fan, Haixia; Cai, Zhiyou (Frontiers in Physiology, 2022)
Adenosine monophosphate-activated protein kinase (AMPK) is a significant energy sensor in the maintenance of cellular energy homeostasis. Autophagy is a highly conserved catabolic process that involves an intracellular degradation system in which cytoplasmic components, such as protein aggregates, organelles, and other macromolecules, are directed to the lysosome through the self-degradative process to maintain cellular homeostasis. Given the triggered autophagy process in various situations including the nutrient deficit, AMPK is potentially linked with different stages of autophagy. Above all, AMPK increases ULK1 activity by directly phosphorylating Ser467, Ser555, Thr574, and Ser637 at least four sites, which increases the recruitment of autophagy-relevant proteins (ATG proteins) to the membrane domains which affects autophagy at the initiation stage. Secondly, AMPK inhibits VPS34 complexes that do not contain pro-autophagic factors and are thus involved in isolation membrane forming processes, by direct phosphorylation of VPS34 on Thr163 and Ser165. After phosphorylation, AMPK can govern autophagosome formation through recruiting downstream autophagy-related proteins to the autophagosome formation site. Finally, the AMPK-SIRT1 signaling pathway can be activated by upregulating the transcription of autophagy-related genes, thereby enhancing autophagosome-lysosome fusion. This work reviews the role of AMPK in different stages of autophagy.